2021
DOI: 10.1007/s12571-021-01200-9
|View full text |Cite
|
Sign up to set email alerts
|

A latent growth curve modelling approach to seasonal and spatial dynamics of food security heterogeneities in rural Lake Naivasha Basin, Kenya

Abstract: The increasing complexity of food insecurity, malnutrition, and chronic poverty faced by Sub-Saharan Africa warrants urgent categorisation and tracking of household food security along both temporal and spatial dimensions. This will help to effectively target, monitor and evaluate population-level programs and specific interventions aimed at addressing food insecurity. Traditional longitudinal analysis does not address the dynamics of inter- and intrahousehold heterogeneities within the seasonal and spatial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…As this indicator is standardized, it can be used to compare the state of households' food security in different locations and over time [29]. Moreover, validation studies have demonstrated that the FCS is a proxy indicator of household caloric availability [30,31].…”
Section: Variablesmentioning
confidence: 99%
“…As this indicator is standardized, it can be used to compare the state of households' food security in different locations and over time [29]. Moreover, validation studies have demonstrated that the FCS is a proxy indicator of household caloric availability [30,31].…”
Section: Variablesmentioning
confidence: 99%
“…Guha and Chandra (2021) derive reliable and representative estimates of food insecurity indicators at district level for the state of Uttar Pradesh in India, using a multivariate small area estimation technique. The approach used by Sassi and Trital (2021) highlights the temporal and spatial dynamics of food security, and relied on a multigroup piecewise latent growth curve to model food security at household level in Kenya. Odhiambo, et al (2021) compare an objective and subjective weighting approach for including the compo nent of natural resources and resilience in the Global Food Security Index.…”
Section: Sustainable Food Securitymentioning
confidence: 99%